Meat : identification, fabrication, utilization - Schneller, Thomas (Australia : Cengage Learning Asia Pte Ltd, 2010)
A manual on purchasing and fabricating meat cuts. It offers information on fabricating beef, pork, veal, lamb, and exotic meats. It also offers storage information, basic preparation methods for each cut, and recipes. It is suitable for chefs, foodservice managers, purchasing agents, culinary students and instructors, and food enthusiasts.
What is meat? -- Beef -- Veal -- Pork -- Lamb -- Game -- Safety and sanitation -- Nutrition -- Recipes.
Includes index.
Keywords: MEAT